Esthesioneuroblastoma Presenting With Orbital Hypertelorism and Foster-Kennedy Syndrome. Issue 8 (November 2021) - Shah, Saumya M.; Halbach, Caroline S.; Wagner, Lilly H.
Abstract : Abstract: Esthesioneuroblastoma is a rare neoplasm originating from the olfactory neuroepithelium at the cribriform plate. The superior nasal cavity is primarily affected. Morbidity and mortality are related to locally destructive growth as well as metastatic potential. Orbital involvement is associated with decreased survival. The authors describe a case of advanced esthesioneuroblastoma with bilateral orbital involvement, presenting with a rare constellation of orbital hypertelorism and Foster-Kennedy Syndrome.